Better to stay downtown or in the countryside? Raptors wintering in urban and rural Protected Areas of Rome (Central Italy) (Avocetta, 2019)
Urbanization is one of the main permanent landscape changes we are witnessing. Some raptor species are increasing their urban population sizes but others are facing local extinctions due to new settlements. To investigate the composition of raptor community and abundance, we counted wintering raptors in five Protected Areas, three located inside an urban environment and two situated in a large part of the countryside around the city. The most abundant species were the Eurasian Kestrel Falco tinnunculus and the Common Buzzard Buteo buteo. The first species was distributed across both landscape types whereas the second required woodland to overwinter. Both species actively selected undisturbed open areas with natural vegetation and tended to avoid artificial surfaces. The results suggest that larger rural areas better support wintering raptor communities than urban contexts, in particular when rural areas are located along the coastline.
Keywords: Protected Areas; Common Buzzard; Eurasian Kestrel; urbanization; wintering raptors